2007
DOI: 10.1084/jem.20061675
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 25 promotes the initiation of proallergic type 2 responses

Abstract: The molecular mechanisms underlying the initiation of innate and adaptive proallergic type 2 responses are not understood. Interleukin (IL) 25, a member of the IL-17 cytokine family, was recently reported (Owyang, A.M., C. Zaph, E.H. Wilson, K.J. Guild, T. McClanahan, H.R. Miller, D.J. Cua, M. Goldschmidt, C.A. Hunter, R.A. Kastelein, and D. Artis. 2006. J. Exp. Med. 203:843–849; Fallon, P.G., S.J. Ballantyne, N.E. Mangan, J.L. Barlow, A. Dasvarma, D.R. Hewett, A. McIlgorm, H.E. Jolin, and A.N. McKenzie. 2006.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
609
3
10

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 504 publications
(633 citation statements)
references
References 27 publications
11
609
3
10
Order By: Relevance
“…12 The presence of this alteration was confirmed by matrix assisted laser desorption/ionisation time of flight (MALDI-TOF) copy number analysis (Figure 1b) and encompassed the gene encoding IL25, a cytokine known to induce Th2 immune responses. 8,9 In vitro analysis of IL25 gene expression in purified lymphocytes following T-cell activation found that this cytokine was expressed at levels 2.49-fold higher in case lymphocytes, compared with lymphocytes from control subjects (t-test P-value ¼ 0.001, Figure 1c). We therefore hypothesized that genetic amplification and overexpression of IL25 in this case may skew immunity towards Th2 responses and thereby result in insufficient Th1 immune responses.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…12 The presence of this alteration was confirmed by matrix assisted laser desorption/ionisation time of flight (MALDI-TOF) copy number analysis (Figure 1b) and encompassed the gene encoding IL25, a cytokine known to induce Th2 immune responses. 8,9 In vitro analysis of IL25 gene expression in purified lymphocytes following T-cell activation found that this cytokine was expressed at levels 2.49-fold higher in case lymphocytes, compared with lymphocytes from control subjects (t-test P-value ¼ 0.001, Figure 1c). We therefore hypothesized that genetic amplification and overexpression of IL25 in this case may skew immunity towards Th2 responses and thereby result in insufficient Th1 immune responses.…”
Section: Resultsmentioning
confidence: 99%
“…These include the Th1-associated cytokine IL12, the Th2-associated cytokine IL5, and more recently, a newly defined member of the IL17 family, IL25, has been shown to promote Th2 responses. 8,9 Here, we describe the molecular characterization of a novel immunodeficiency disorder. This case shows profound combined immunodeficiency that manifested from an early age with recurrent Varicella infections, bronchitis, skin infections, upper respiratory tract infections and otitis media (For detailed case history, see Supplementary Information).…”
Section: Introductionmentioning
confidence: 99%
“…The expression levels of all mRNAs from untreated DC/T-cell culture represented one fold. Primer pairs used for IL-4, IL-5, IL-13, IFN-g, GATA-3, and T-bet were described previously [59].…”
Section: Real-time Pcr Analysismentioning
confidence: 99%
“…The expression levels of all mRNAs from untreated DC/T-cell culture represented one fold. Primer pairs used for IL-4, IL-5, IL-13, IFN-g, GATA-3, and T-bet were described previously [59].IgG isotype spectrum analysis C57BL/6 mice were immunized with 100 mg OVA (SigmaAldrich)1DMSO (control), me-Ant K (50 mg), or LPS (10 mg) via subcutaneous injection and boosted with the same mixtures 14 days later. Mouse sera were collected after 30 days, and OVAspecific IgG isotypes were determined by direct ELISA [60].…”
mentioning
confidence: 99%
“…Chronic over-expression of IL-25 in the airway epithelium resulted in asthma features such as mucus production, and airway infiltration of eosinophils and macrophages. 36 Work in this area of Th17 cytokines in the lung have actively been pursued for many pulmonary disease models.…”
Section: Transgenic Expression Of Th17 In the Lungmentioning
confidence: 99%